2006
DOI: 10.1103/physrevb.73.140405
|View full text |Cite
|
Sign up to set email alerts
|

Short-range ordered phase of the double-exchange model in infinite dimensions

Abstract: Using dynamical mean-field theory, we have evaluated the magnetic instabilities and T = 0 phase diagram of the double-exchange model on a Bethe lattice in infinite dimensions. In addition to ferromagnetic (FM) and antiferromagnetic (AF) phases, we also study a class of disordered phases with magnetic short-range order (SRO). In the weak-coupling limit, a SRO phase has a higher transition temperature than the AF phase for all fillings p below 1 and can even have a higher transition temperature than the FM phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…In a typical spin glass, such as CuMn [8], the RKKY interactions between randomly alloyed Mn ions produce a disordered ground state with a massive degeneracy. Recent work [9] on the DE model has revealed that the competing RKKY interactions between magnetic moments on a Bethe lattice can stabilize a phase with short-range but not longrange magnetic order [10]. We now show that the magnetic susceptibility of this SGL phase has a cusp at T SGL , marking the onset of short-range order, and reaches a nonzero value as T !…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…In a typical spin glass, such as CuMn [8], the RKKY interactions between randomly alloyed Mn ions produce a disordered ground state with a massive degeneracy. Recent work [9] on the DE model has revealed that the competing RKKY interactions between magnetic moments on a Bethe lattice can stabilize a phase with short-range but not longrange magnetic order [10]. We now show that the magnetic susceptibility of this SGL phase has a cusp at T SGL , marking the onset of short-range order, and reaches a nonzero value as T !…”
mentioning
confidence: 54%
“…But as shown in Ref. [9] using dynamical mean-field theory (DMFT), the competing FM and AF interactions may actually favor a SGL phase over the ordered phases for small J H .…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Such polarons apparently affect the magnetic and electric properties at high temperatures. Calculations in the double exchange model [41] show the existence of a short range ordered magnetic phase at T = 0 and its conservation at T > T C . The transition to a low sym metry orthorhombic phase with Jahn-Teller distor tions can be assumed to contribute to the localization of carriers.…”
Section: Discussionmentioning
confidence: 96%